Discovery of a new predominant cytosine DNA modification that is linked to gene expression in malaria parasites - Hammam, Elie (2020)
DNA cytosine modifications are key epigenetic regulators of cellular processes in mammalian cells, with their misregulation leading to varied disease states. In the human malaria parasite Plasmodium falciparum, a unicellular eukaryotic pathogen, little is known about the predominant cytosine modifications, cytosine methylation (5mC) and hydroxymethylation (5hmC). Here, we report the first identification of a hydroxymethylcytosine-like (5hmC-like) modification in P. falciparum asexual blood stages using a suite of biochemical methods. In contrast to mammalian cells, we report 5hmC-like levels in the P. falciparum genome of 0.2–0.4%, which are significantly higher than the methylated cytosine (mC) levels of 0.01–0.05%. Immunoprecipitation of hydroxymethylated DNA followed by next generation sequencing (hmeDIP-seq) revealed that 5hmC-like modifications are enriched in gene bodies with minimal dynamic changes during asexual development. Moreover, levels of the 5hmC-like base in gene bodies positively correlated to transcript levels, with more than 2000 genes stably marked with this modification throughout asexual development. Our work highlights the existence of a new predominant cytosine DNA modification pathway in P. falciparum and opens up exciting avenues for gene regulation research and the development of antimalarials.